Defense of the right to live in the city of the paraguayan community Corumba Kue from the university extension - Pereira Cardozo, Hugo Javier (2024)
The construction of a tourist complex on an island located in front of a community in the metropolitan area of Asunción, Paraguay, known as Corumba Kue, aroused the concern of many families who see the venture as a risk to their permanence in the place. This motivated the proposal and execution of an extension project between the university and the community. The main objective of this article was to analyze the contribution of the university extension project, from a critical perspective, to the defense of the right to the city of the community’s residents. Interviews and public interventions from community leaders were recovered. Some official documents were also analyzed. Some journalistic articles were also considered that helped to better understand the context. The study achieved within the framework of the execution of the university extension project is valued by the leaders of the community as documentary evidence that allows them to engage in a debate in better conditions with the state authorities and the business sector in their fight for their right to live in the city. The experience of the executed project shows that horizontal work with communities, carrying out consultations on their projections and concerns allows contributions to be made that support the construction of cities that take into account the voices of all their citizens.